Morphometric diversity of Zabrus morio (Coleoptera: Carabidae) in relation to sex and altitude in Uzbekistan's mountain ecosystems - DILNOZA F. ZOKIROVA; JASUR A. KUDRATOV; RAFIK A. KHAMZAEV; ASOLAT B. KHAMIDOVA; BEKSOD OTAKULOV; GULRUH URINOVA; IRODA ZOHIDOVA; ERKIN ABDULLAEV; FARIZA RAYIMOVA; ABDUVAET PAZILOV; SHAHLO TURSUNOVA; MUNISA BAKHRILLAYEVA; FAZLITDIN Z. KHALIMOV (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Zokirova DF, Kudratov JA, Khamzaev RA, Khamidova AB, Otakulov B, Urinova G, Zohidova I, Abdllaev E, Rayimova F, Pazilov A, Tursunova S, Bakhrillayeva M, Khalimov FZ. 2025. Morphometric diversity of Zabrus morio (Coleoptera: Carabidae) in relation to sex and altitude in Uzbekistan's mountain ecosystems. Biodiversitas 26: 4730-4745. Zabrus morio is the only representative of the genus Zabrus in Uzbekistan, considered a potential pest and widely distributed in mountainous and foothill ecosystems. Studying its morphometric characteristics is important for understanding population traits and adaptive responses. A total of 115 individuals (50 females, 65 males) from 10 sites along an altitudinal gradient were examined. Sites above 1,200 masl were represented by mountain steppes, subalpine meadows, juniper woodlands, and alpine meadows. Sites below 1,200 m were characterized by arid ephemeral-grass steppes, sagebrush-ephemeral steppes, and shrub-steppe communities. Ten morphometric traits were measured using a binocular microscope. Head length was the most variable trait (CV = 10.2%), while elytral width was the least variable (CV = 5.5%); in general, body length parameters were more variable than widths. The strongest correlation was found between elytra length and total body length (r = 0.93), while head length and pronotum length were the most independent traits (r = 0.49). Females showed greater variability in head dimensions and pronotum length, while males exhibited higher variability in elytral width and interocular distance. In females, elytra length correlated most strongly with total body length (r = 0.92), whereas in males, head width closely correlated with pronotum width (r = 0.95), which may indicate a relationship between head size and pronotum size. Overall, trait variability decreased with increasing altitude, with only male head length showing a statistically significant reduction. These findings emphasize the adaptive morphometric variability of Z. morio depending on sex and ecological conditions, as well as the potential implications of these correlations for the species’ ecology and evolution.